Reasonable Notice for Wrongful Dismissal: Court versus Human Resource Decisions - Lam, Helen; Devine, Kay (Relations industrielles / Industrial Relations, 2001)
SummaryThis study identifies and compares the severance compensation determinants of legal and human resource (HR) professionals, using court cases and a policy-capturing HR survey. Results confirmed that HR practitioners not only considered the factors critical in court decisions, which were length of service, age, employment status, and labour market conditions, but also had economic and social justice concerns as revealed by significant factors such as a company’s financial situation and reason for dismissal. Certain HR decision-makers’ characteristics were also found to influence the decisions. Overall, HR notices were shorter than court notices in similar situations. Implications of such findings are discussed.